(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
Soil algae are photosynthetic microorganisms showing huge differences in morphology depending on the soil type, agricultural practices, and environmental factors. The aim of this research was to compare the results of classical and molecular protocols for microalgal identification. The green microalgae were isolated from acidic arable soil of dystric cambisol type, using BG11 medium and the agar plate method. Firstly, the identification of the microalgae was performed based on its morphological characteristics using light microscopy (LM) and taxonomic monographs and reference books. The isolate was initially annotated on genus level as Coelastrella sp. Gene marker (ITS2) was used for molecular identification. According to this protocol, the microalga was identified as Scenedesmus vacuolatus. Combination of morphology and DNA-based approach proved to be the most effective for obtaining a consistent species level identification. Moreover, this is the first record of Scenedesmus vacuolatus identification from soil in Vojvodina, Serbia. Bangladesh J. Plant Taxon. 30(2): 255-261, 2023 (December)